TRENDS IN THE DEVELOPMENT OF INNOVATIVE TECHNOLOGIES IN SMALL ENTERPRISES OF HOTEL BUSINESS IN CRISIS - Svetlana A. Lankina; Tatiana E. Platonova (Статистика и экономика, 2016)
The article considers the problems of innovative crisis management on the exampleof the hotel complex, operating in the Republic of Khakassia (Eastern Siberia), thespeciﬁc data of the economic activity of theenterprise, analyzed the ways out of thecrisis based on an innovative approach.